Hyperoside Supplementation in Preservation Media Surpasses Vitamin C Protection Against Oxidative Stress-Induced Damages in Human Spermatozoa - Moreira, Mafalda V (2022)
Oxidative Stress (OS) is reported as one of the main causes of male infertility. Infertile couples often resort to assisted reproductive technology (ART) to achieve parenthood. However, preparation for ART protocols increases the exposer of gametes to OS. Thus, it is crucial to find suitable preservation media that can counteract the OS-induced damages in spermatozoa. In this work, we tested and compared the efficiency of vitamin C (VC) and hyperoside (HYP) as potential antioxidant supplements for sperm preservation media.